The Commercial Antibodies Widely Used to Measure H3 K56 Acetylation Are Non-Specific in Human and Drosophila Cells. - Pal, S.; Graves, H.; Ohsawa, R.; Huang, T.H.; Wang, P.; Harmacek, L.; Tyler, J. (PLoS ONE, 2016)
Much of our understanding of the function of histone post-translational modifications in metazoans is inferred from their genomic localization and / or extrapolated from yeast studies. For example, acetylation of histone H3 lysine 56 (H3 K56Ac) is assumed to be important for transcriptional regulation in metazoan cells based on its occurrence at promoters and its function in yeast. Here we directly assess the function of H3 K56Ac during chromatin disassembly from gene regulatory regions during transcriptional induction in human cells by using mutations that either mimic or prevent H3 K56Ac. Although there is rapid histone H3 disassembly during induction of some estrogen receptor responsive genes, depletion of the histone chaperone ASF1A/B, which is required for H3 K56 acetylation, has no effect on chromatin disassembly at these regions. During the course of this work, we found that all the commercially available antibodies to H3 K56Ac are non-specific in human cells and in Drosophila. We used H3-YFP fusions to show that the H3 K56Q mutation can promote chromatin disassembly from regulatory regions of some estrogen responsive genes in the context of transcriptional induction. However, neither the H3 K56R nor K56Q mutation significantly altered chromatin disassembly dynamics by FRAP analysis. These results indicate that unlike the situation in yeast, human cells do not use H3 K56Ac to promote chromatin disassembly from regulatory regions or from the genome in general. Furthermore, our work highlights the need for rigorous characterization of the specificity of antibodies to histone post-translational modifications in vivo.